Welcoming AFP's Patient Partners - Lin, Kenneth W., MD, MPH; Haskell, Helen, MA; James, John, PhD; Sexton, Sumi M., MD (American family physician, 2020)
In her home state of South Carolina, she successfully advocated for the passage of the Lewis Blackman Patient Safety Act, focused on transparency and communication, and the Hospital Infections Disclosure Act, a state-level precursor to public reporting from the Centers for Medicare and Medicaid Services. In addition to holding leadership roles with the nonprofit organizations Mothers Against Medical Error (which she founded) and Consumers Advancing Patient Safety, Helen serves on the boards of directors of the Institute for Healthcare Improvement and the Accreditation Council for Graduate Medical Education. Between 2007 and 2019, the recently retired Close-ups feature told patients’ stories in their own words.5 So, why enter into a formal partnership now? A national survey fielded by the Right Care Alliance Patient Council between November 2018 and March 2019 found that many patients are worried about being misdiagnosed, receiving unnecessary or harmful treatment, and not receiving enough information to make good medical decisions.6 In addition, coronavirus disease 2019 (COVID-19) has widened the patient-clinician divide because the fear of exposure to severe acute respiratory syndrome coronavirus 2, tight finances, and loss of health insurance have dramatically reduced outpatient visits, despite the expansion of telemedicine.7 In addition to other initiatives that AFP is launching to respond to the pandemic,8 we hope to involve our patient partners in developing new strategies to help family physicians address the evolving concerns of patients in the COVID-19 era.